Effect of nanoparticle shape on the mixed convective transport over a vertical cylinder in a non-Darcy porous medium. (April 2022) - Hemalatha, R.; Kameswaran, Peri K.; Murthy, P.V.S.N.
Abstract: The current article depicts the mixed convective flow of Graphene oxide and Clay nanoparticles suspended nanofluid in a non-Darcy porous medium considering the effect of the shape of the nanoparticles. The nanofluid utilized in the present study is a drilling fluid, which is mud that circulates in the cylindrical borehole, to enhance the drilling operation efficiency leading to cost effectiveness. The drilling fluid used to lubricate and cool the drill bit, improves the productivity and stability, lifts the cuttings from the bottom of the hole. The current investigation is to improve the efficiency of the drilling fluid. Here the base fluid is considered as water based mud and the nanoparticles are GO and Clay . The spherical and needle shaped nanoparticles are investigated in this study. The basic equations are solved numerically by adopting the shooting technique. It is also noticed that more heat augmentation is seen in the Darcy flow compared to the non-Darcy flow conditions. The results show that a strengthened temperature distribution is noticed with the spherical shaped particles, as the nanoparticle volume fraction increases in the base fluid. The present findings and the findings in the literature have proportionality. The sphere shaped particles have the higher settling rate which helps in drill cutting.